2014
DOI: 10.1002/qre.1694
|View full text |Cite
|
Sign up to set email alerts
|

A New Maximum Exponentially Weighted Moving Average Control Chart for Monitoring Process Mean and Dispersion

Abstract: Maximum exponentially weighted moving average (MaxEWMA) control charts have attracted substantial interest because of their ability to simultaneously detect increases and decreases in both the process mean and the process variability. In this paper, we propose new MaxEWMA control charts based on ordered double ranked set sampling (ODRSS) and ordered imperfect double ranked set sampling (OIDRSS) schemes, named MaxEWMA‐ODRSS and MaxEWMA‐OIDRSS control charts, respectively. The proposed MaxEWMA control charts are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…For a fair comparison, we used the same control‐chart parameters and in‐control ARL 0 value of 200 for all the schemes. The control charts used for comparison include the MCE by Zaman et al, the ODRSS and OIDRSS by Haq et al, the CS‐EWMAT by Abbas et al, and the CS‐EWMA‐V by Zaman et al Others are the HHW1 and HHW2 charts by Huwang et al; the ln( S 2 ), χ S , and P S by Shu; the CUSUM‐ S 2 by Castagliola et al; and the EWMA‐ S 2 by Castagliola …”
Section: Performance Analysis and Comparisonsmentioning
confidence: 99%
“…For a fair comparison, we used the same control‐chart parameters and in‐control ARL 0 value of 200 for all the schemes. The control charts used for comparison include the MCE by Zaman et al, the ODRSS and OIDRSS by Haq et al, the CS‐EWMAT by Abbas et al, and the CS‐EWMA‐V by Zaman et al Others are the HHW1 and HHW2 charts by Huwang et al; the ln( S 2 ), χ S , and P S by Shu; the CUSUM‐ S 2 by Castagliola et al; and the EWMA‐ S 2 by Castagliola …”
Section: Performance Analysis and Comparisonsmentioning
confidence: 99%
“…Salazar and Sinha 20 were first to develop control charts for monitoring the process mean using RSS and showed that their proposed charts performed better than those charts based on the SRS. Muttlak and Al-Sabah, 21 Abujiya and Muttlak,22 Al-Omari and Haq, 23 Abujiya et al, 24 Mehmood et al, 25 Abujiya et al, 26 and Haq et al [27][28][29] are the major references on the development of control charts using the RSS technique, but no one has given devotion to develop a control chart based on the RSS method with nonparametric approach. So, in this study, we used the RSS method under the scenario of nonparametric approach for development of control chart to monitor the process target.…”
Section: And the Reference Thereinmentioning
confidence: 99%
“…Recently, the technique has found its way into the area of the statistical quality control. For example, see Abujiya and Muttlak, Al‐Sabah, Jafari and Mirkamali, Al‐Omari and Haq, Mehmood et al ., Haq et al ., Abujiya et al ., Haq et al ., Abujiya et al ., Haq and Al‐Omari, and Mehmood et al ., to name but a few. Comprehensive review on the theory, methods, and applications of RSS can be found in Wolfe .…”
Section: Design Of Combined Shewhart–cumulative Sum S Chart Using Extmentioning
confidence: 99%